Emotional Separation among Some Wives in the Municipality of the Capital, Sana’a: An Exploratory Study in Light of the Repercussions of the War for the Period 2015–2023 - Al-Baddai, Nasser Ali (University of Science and Technology Journal for Management and Human Sciences, 2024)
This study aimed to find out the extent of emotional separation among wives residing in the capital Sana’a in Yemen in light of the repercussions of the ongoing war (2015-2023). The study followed the descriptive approach, and a questionnaire was distributed to a sample of (103) wives in the capital Sana’a who suffer from a case of emotional separation from their husbands. They were chosen randomly. The results indicated moderate levels of emotional separation in multiple axes: (emotional, social, and economic). The psychological and physical axis also came in at a high degree. The husband’s educational level had a significant impact on the degree of separation. Overall and specifically on the “emotional” axis, where the husband’s educational qualifications at the primary level were associated with greater separation, the wife’s economic level also affected the overall grades and on the social, economic, and emotional dimensions, where lower economic status was associated with higher separation. It is worth noting that no differences emerged based on variables, such as: duration of marriage, housing ownership, or work status, but the type of housing (such as living with the husband’s family or a co-wife) showed an association with greater separation on both the economic and psychological-physical levels. Finally, the filial dimension was associated with higher scores on the “emotional” axis.